Utilization of Learning Media Based on Culap-culip Animated Video in Optimizing the Formation of Elementary School Students’ Morals - Lestari, Naya Dwi; Utami, Ratnasari Diah (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to describe the utilization of Culap-culip animated video-based learning media, identify supporting and inhibiting factors, and propose effective solutions to overcome obstacles in optimizing the moral formation of grade 3 students at SDIT Nur Hidayah. Methodology: The study employed a descriptive qualitative approach with a phenomenological design. Data were collected through observation, interviews, and documentation. Data validity was ensured using source triangulation and technique triangulation, while data analysis included data reduction, data display, and conclusion drawing. Results: The results indicate that the integration of Culap-culip animated video-based media into Islamic Personal Development subjects significantly contributed to the moral development of grade 3 students. Positive behavioral changes were observed, including increased awareness of honesty, discipline, politeness, and responsibility. The effectiveness of the moral formation process was supported by enabling factors and was further reinforced by strategies to overcome implementation challenges. Applications/Originality/Value: This research provides evidence of the effectiveness of animated video-based learning media in character education, particularly in instilling core moral values at the primary school level. It highlights how media tailored to students’ developmental stages can be a valuable educational tool, offering practical insights for educators and curriculum developers seeking to promote values-based learning through engaging and contextually relevant media content.